Survey on network function virtualization in RAN - Haiyu JIA; Jia CHEN; Mingxin WANG (Dianxin kexue)
Network function virtualization (NFV) is a kind of new network technology rising in recent years. It realizes the decoupling of software and hardware by running the software which has specific function on a general-purpose hardware server. Applying the NFV to the radio access network could virtualize some of the radio access functions. It can reduce the operating costs and capital costs efficiently, and improve the flexibility of the network deployment. It also can satisfy the quality of experience of mobile users. In order to review the work that contribute to the current situation of NFV in radio access network, three perspectives were reviewed, including research on the related standards of network functional virtualization in RAN, network architecture of network function virtualization, and the resource allocation of network function deployment. Finally, the challenges of network function virtualization applying in wireless network were proposed.